indonesia KOMPOSIT ASPAL BETON (AC-WC) DENGAN PENAMBAHAN FLY ASH DAN RUBBER WASTE UNTUK PERKERASAN JALAN - Juny Andry Sulistyo; Krisna Majid; M. Azrul; Bunga Permata (Jurnal Teknik SILITEK, 2024)
Road infrastructure plays an important role in connectivity, mobility, and economic growth. In Indonesia, road damage is often caused by heavy loads, heavy traffic, and environmental changes. This study aims to improve the quality of asphalt by mixing Asphalt Concrete Wearing Course (AC-WC) with Fly Ash and Rubber Waste. Fly Ash, with a silica content of 46.7% and Rubber Waste, which has a high viscosity at a temperature of 60°C, are used as substitutes for stone ash and sand.The study was conducted at the Engineering Laboratory of Sultan Agung Islamic University, Semarang using a mixture of Fly Ash at a percentage of 0%, 2%, 4% and 6%, and Rubber Waste 0%, 1%, 2%, and 3% of the weight of the test specimen. After making 48 test specimens, Marshall testing was carried out using the Marshall Compression Machine.The results showed that the addition of Fly Ash and Rubber Waste affected the stability of the asphalt, with the Marshall Quotient value decreasing compared to the normal mixture. The decrease was caused by the large number of cavities in the test specimens. The Marshall stability optimization value for the variation of Fly Ash 6%, Rubber Waste 1% is 814.81 kg/mm ​​and for the variation of Fly Ash 6%, Rubber Waste 2% is 804.99 kg/mm.